2011
DOI: 10.2165/11594980-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Therapy Cost Analysis in the US

Abstract: BackgroundBloodstream infections (BSI) occur in up to 350 000 inpatient admissions each year in the US, with BSI rates among patients receiving parenteral nutrition (PN) varying from 1.3% to 39%. BSI-attributable costs were estimated to approximate $US12000 per episode in 2000. While previous studies have compared the cost of different PN preparation methods, this analysis evaluates both the direct costs of PN and the treatment costs for BSI associated with different PN delivery methods to determine whether co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…In another study, patients receiving MCB incurred lower health-care costs compared with the compounded PN group. 23 Given the retrospective design of this study, we were only able to assess variables that were included within the patient's medical chart and on our CRFs. Therefore, if patients received central line catheter placement before their admission, their central line catheter was undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, patients receiving MCB incurred lower health-care costs compared with the compounded PN group. 23 Given the retrospective design of this study, we were only able to assess variables that were included within the patient's medical chart and on our CRFs. Therefore, if patients received central line catheter placement before their admission, their central line catheter was undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous economic analyses assessing the costs of nutrition therapy, which have largely been based on evidence of effectiveness of questionable methodological quality and taken a narrow focus on upfront acquisition costs,20 our CMA is based on the results of a multicenter clinical trial conducted in a focused patient population10 using published costs obtained from comprehensive databases with a broad perspective 14,15. Although our findings of significant and substantial cost savings may appear to conflict with a recent economic analysis reporting increased costs attributable to parenteral nutrition,19 this previously published economic analysis addressed a different clinical indication for parenteral nutrition than did our CMA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these US cost estimates, and the cost estimates for parenteral nutrition, were generated from robust databases containing tens of thousands of transactions fromhundreds of hospitals 14,15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this study, it was determined that the frequency, severity, and extent of medication errors in all hospital wards demonstrated that parenteral nutrition mistakes were considered as risky medication errors (Turpin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%